FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PEDIKULOSIS KAPITIS PADA SANTRI PUTRI PONDOK PESANTREN DI BANTUL YOGYAKARTA - Mudita Sri Hidayah (STIKes Surya Global Yogyakarta, 2019)
Background: Health problem is a very complex problem and one of these is skin disease’s problem. Pediculosis capitis is one of the high cases of skin disease where its prevalence of children at school age. This disorder does not attract the attention of many clinical, but it can cause significant morbidity. Many factors that cause prevalence of Pediculosis capitis are density residential, social, economic, personal hygiene, behavior, personal characteristics, knowledge, and others. It is said from the information of board of Fadlun Minalloh Boarding School that in this boarding school is discovered more than 70% of students suffer from Pediculosis capitis. Objective: to determine the factors that related with the occurrence Pediculosis capitis in that boarding school.Method: This study is an observational analytic research by using cross sectional design, technique sampling used inclusion criteria. The samples are 33 respondents. The instrument used questionnaires and checklist. It uses univariate analyzing in data analysis technique and bivariate analysis with Fisher statistical test to determine the value of p, CI, and the Prevalence Ratio.Results: The results of this research shows that from 33 respondents are obtained 31 respondents (93.9%) suffered from Pediculosis capitis, while those who do not suffer from Pediculosis capitisare 2 respondents (6.1%). Bivariate analysis for personal hygiene with the incidence Pediculosis capitis p value = 0.419 and RP = 0,1,45 (95% CI: 0.650 to 3.236), for using of goods alternately with events Pediculosis capitis no correlation between the using of goods alternately with events Pediculosis capitis value of p = 0.419 and RP = 0,1,45 (95% CI: 0.650 to 3.236, and for knowledge with the occurrence of Pediculosis capitis p = 1.0 and RP = 1.074 (95% CI: 0.973 to 1.186). Conclusion: there is no significant correlation between personal hygiene, using of alternate goods, and knowledge with Pediculosis capitis of female students in boarding school Fadlun Minalloh Bantul, Yogyakarta.